The Relationship between Sport Perfectionism and Mental Skills in Taekwondo Athletes - Hassan Gharayagh Zandi; Mahmoud Mohebi; Sahar Zarei (University of Tehran, 2020)
Taekwondo athletes experience a lot of pressure during the competition, because they must attack and defend at the same time, In addition, before the competition, the stress of the taekwondo athletes increases and lose weight quickly, In this context, the maintenance of desirable psychological states and success in Taekwondo requires a set of specific psychological factors, such as positive perfectionism and psychological skills. Therefore the aim of this research was to survey the relationship between Sport perfectionism and mental skills in Taekwondo Athletes. Present study research method was descriptive - correlational, Statistic population was included all of from Iranian Taekwondo athletes participated in country championship competition. Samples were 110 males with average age of (23/60 ± 5/84) selected based on random sampling, and completed the Scales of perfectionism and mental skills. The data was analyzed by Pearson correlation and multiple regression (inward method) tests. The results of Pearson correlation revealed that positive perfectionism was positively associated with mental skills of foundation, psychosomatic and cognition, and Negative perfectionism had the negative correlation with these mental skills (p < 0/01). Regression analysis showed that positive and negative perfectionism dimensions predict 40 percent of total mental skills variance (p < 0/05). According to the findings, it seems that dimensions of perfectionism have an important role in selecting mental skills and the level of skills which every Taekwondo Athletes uses is correlated with these dimensions.